The prevalence and treatment of hypertension in the elderly population of the Mexican Institute of Social Security Prevalencia y tratamiento de hipertensión en ancianos en el Instituto Mexicano del Seguro Social - Carmen García-Peña; Margaret Thorogood; Sandra Reyes; Jorge Salmerón-Castro; Carlos Durán (Instituto Nacional de Salud Pública, 2001)
Objective. To assess the prevalence and treatment of high blood pressure among elderly people in Mexico. Material and Methods. A cross-sectional study was conducted from February to July 1998 among the elderly people covered by the Instituto Mexicano del Seguro Social (IMSS) healthcare services in Mexico City. The study population consisted of 4 777 subjects aged 60 years and over, selected from a cohort of 5 433 people, representative of the population of Mexico City. Trained nurses carried out three blood pressure measurements at home. Diagnosis of high blood pressure was established if systolic pressure was equal to or higher than 160 mmHg, and/or diastolic pressure was equal or higher than 90 mmHg, or by self-report of a medical diagnosis of hypertension. Demographic and risk factor information was also collected. Results. A total of 4 777 subjects were screened; 2 036 (43%) of them reported that they had been previously diagnosed as hypertensive. Of these, 1 954 (96%) were already on pharmacological treatment. A further 273 (5.7%) subjects were found to be hypertensive at screening. Among those receiving treatment, 1 399 (68.5%) had a blood pressure reading of less than 160/90 mmHg, and this was also the case for 59 (72%) of the known hypertensives not on treatment. A single drug was used by 1 556 (79.6%) of those on treatment. Risk factors for hypertension were more frequent in the hypertensive group (p£0.05). Conclusions. Almost half of the elderly population is hypertensive, most of them are already on treatment, but about one third of those on treatment do not have an adequate control of high blood pressure. The English version of this paper is available too at: http://www.insp.mx/salud/index.html Objetivo. Determinar la prevalencia y el tratamiento de la hipertensión arterial en ancianos en México. Material y métodos. De enero a julio de 1998, se llevó a cabo un estudio transversal en ancianos derechohabientes del Instituto Mexicano del Seguro Social. La población de estudio consistió de 4 777 ancianos, seleccionados de una cohorte representativa de 5 433 sujetos residentes en el Distrito Federal. Enfermeras entrenadas midieron tres veces la presión arterial en el domicilio de los sujetos de estudio. Se diagnosticó hipertensión arterial si la presión sistólica era igual o mayor a 160 mm Hg y/o si la presión diastólica era igual o mayor a 90 mm Hg o por auto reporte de un diagnóstico médico. Se colectó también información demográfica y sobre factores de riesgo. Resultados. Un total de 4 777 sujetos fueron estudiados y 2 036 (43%) reconocieron un diagnóstico previo de hipertensión; de esos, 1 954 (96/) se encontraban bajo tratamiento farmacológico y 273 (5.7%) fueron hallazgo del tamizaje. El 68.5% (n= 1 399) de aquellos que recibían tratamiento y 59 (72%) de los que reportados como hipertensos no recibían tratamiento, tuvieron una presión arterial de menos de 160/90 mm Hg. De aquellos en tratamiento, 1 556 (79.6%) tomaban un solo medicamento. La frecuencia de factores de riesgo fue más alta en el grupo de hipertensos (p<=0.05). Conclusiones. Casi la mitad de la población anciana estudiada es hipertensa, mucha de ella en tratamiento; sin embargo, una tercera parte de éstos no tienen un adecuado control de la presión arterial. El texto completo en inglés de este artículo está también disponible en: http://www.insp.mx/salud/index.html